Sobre el binomio libertad y seguridad en el derecho (2016)
This paper examines the complex relationship between two key pieces of the ruleof law, freedom and security. Examines, in particular, the current influence of theexpanded concept of security on the fundamental right to personal freedom fromthe idea that the future might hold completely risk scenarios and new dangers.This concept of security points, so the reaction to the targeted phenomena and,ultimately, that purpose also involves the reconfiguration of state tasks and aims, inturn, to a new conception of the state with a clear impact on the idea of freedomand therefore the rule of law itself.For all analyzes, first, the content constitutionally declared the right to freedomand security in the Spanish legal system and to highlight, ultimately, freedomand security, while you goods closely interwoven enroll in the legal order whoseeffectiveness is mission of the State. What refers to the traditional relationshipbetween freedom and common good, the Greek koinon goes to Rome as bonumcommune. Of followed, addresses, just as the freedom-security binomial linkedto the common good. Well, not chance, just enough politically, expressed in Law(Law), produces freedom in safety due to homonoia or consensus on the basic aspects of coexistence. Hence the indivisibility of freedom and security. Then, asindicated above, it delves into the origin and development of current risks affectingthe traditional relationship between freedom and liberty. As proof of the above, itends with the exhibition of its application to a particular field: urbanism. Well, infact, the current situation and the risks involved can be illustrated by its light whilespatial expression of society, the political and economic-social system.